Case Report: Nystagmus as a core presenting sign in pediatric anti-Ma2 antibody-associated cerebellar ataxia: diagnostic implications from clinical and serological profiling - Ma, Jiehui; Yang, Yuting; Li, Zhiyu; Tan, Qianqian; Cao, Pan; Ni, Kun; Cai, Xiaofang; Sun, Dan (Frontiers in Pediatrics, 2025)
BackgroundThe anti-Ma2 antibody is a well-known, specific marker of paraneoplastic limbic and brainstem encephalitis, mainly described in adult, especially in males with testicular germ cell tumor. Pediatric cases remain exceptionally rare. We present a child with anti-Ma2 antibody-associated cerebellar ataxia in whom nystagmus was identified as a core presenting symptom; the diagnosis was confirmed via cell-based assay (CBA).Case presentationAn 11-year-old boy sought medical attention for symptoms such as vomiting, nystagmus, dizziness, slurred speech, and limb weakness. Routine laboratory tests and brain MRI were normal, simultaneously we ruled out infectious factors. Further limb coordination tests suggested the boy may have cerebellar ataxia. Based on clinical symptoms and the above tests, the boy underwent a comprehensive examination for suspected paraneoplastic neurological syndrome (PNS). Serum enzyme-linked immunospot test was positive (+) for anti-Ma2 antibodies and confirmed by CBA with a titer of 1:10. The boy was diagnosed with anti-Ma2 antibody-associated cerebellar ataxia. Subsequently, he received intravenous immunoglobulin (IVIG) and methylprednisolone (mPD) treatment and experienced significant symptomatic improvement. Complete resolution occurred by 38 days post-discharge, sustained through one-year follow-up.ConclusionsNystagmus was first identified in pediatric patients with anti-Ma2 antibody-associated syndrome, expanding clinicians' knowledge of the phenotype in children. Our case demonstrates that IVIG and steroids induced rapid and sustained remission despite presumed cell-mediated immunity cases, with complete symptom resolution within 8 weeks and no recurrence at 1-year follow-up. We also emphasize CBA's superior accessibility and its higher sensitivity and specificity in detecting low-titer antibodies for detecting antibodies in autoimmune encephalitis, particularly in mild or atypical presentations.